2017
DOI: 10.3390/ma10060588
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Characteristic Variation of the FBG Spectrum with Crack Propagation in Aluminum Plate Structures

Abstract: In order to monitor the crack tip propagation of aluminum alloy, this study investigates the variation of the spectrum characteristics of a fiber Bragg grating (FBG), combined with an analysis of the spectrum simulation. The results identify the location of the subordinate peak as significantly associated with the strain distribution along the grating, corresponding to the different plastic zones ahead of the crack tip with various crack lengths. FBG sensors could observe monotonic and cyclic plastic zones ahe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Meanwhile, the subordinate peaks vary with the complex strain distribution along the grating. In addition, the relationship between the subordinate peak and the strain distribution pattern has been discussed and simulated in previous research [13]. The turning subordination peaks coincide with the crack length, which is represented in the comparison between Figures 5(a) and 6(a) with Figure 7(a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the subordinate peaks vary with the complex strain distribution along the grating. In addition, the relationship between the subordinate peak and the strain distribution pattern has been discussed and simulated in previous research [13]. The turning subordination peaks coincide with the crack length, which is represented in the comparison between Figures 5(a) and 6(a) with Figure 7(a).…”
Section: Resultsmentioning
confidence: 99%
“…As the FWHM of reflection spectra increases, reflectance decreases and the subordinate peaks appear initially, and even spectra distortion occurs. Reference [13] investigates the subordinate peak located in the lower wavelength, with quadratic strain distribution being employed along the grating of the fiber. When the cubic strain gradient is employed along the grating of the fiber, the subordinate peak is located at a higher wavelength.…”
Section: Mechanism Of the Skewing Of The Subordinate Wavelengthmentioning
confidence: 99%
See 1 more Smart Citation
“…The yield strength of the materials was 360 MPa, the ultimate strength was 490 MPa, the Poisson's ration was 33, and the Young's modulus was 72,000 MPa. Results from Reference [23] indicate that the pre-crack around the hole has a larger stress concentration and therefore has the most potential to develop the fatigue damage.…”
Section: Specimens: Materials and Geometrymentioning
confidence: 99%
“…Many studies have shown that the FBG reflection spectrum was distorted due to the inhomogeneous strain field caused by damage [7]. Many damage features factors were extracted from the distorted spectra based on the response.…”
Section: Introductionmentioning
confidence: 99%